Induction of Osteopontin Expression by Nicotine and Cigarette Smoke in the Pancreas and Pancreatic Ductal Adenocarcinoma Cells - Chipitsyna, Galina (Int J Cancer, 2009)
Pancreatic ductal adenocarcinoma (PDA) is a lethal disease with etiological association with cigarette smoking. Nicotine, an important component of cigarettes, exists at high concentrations in the bloodstream of smokers. Osteopontin (OPN) is a secreted phosphoprotein that confers on cancer cells a migratory phenotype and activates signaling pathways that induce cell survival, proliferation, invasion, and metastasis. Here, we investigated the potential molecular basis of nicotine’s role in PDA through studying its effect on OPN. Nicotine significantly (p<0.02) increased OPN mRNA and protein secretion in PDA cells through activation of the OPN gene promoter. The OPN mRNA induction was inhibited by the nicotinic acetylcholine receptor antagonist, mechamylamine. Further, the tyrosine kinase inhibitor genistein inhibited the nicotine-mediated induction of OPN, suggesting that mitogen activated protein kinase signaling mechanism is involved. Nicotine activated the phosphorylation of ERK1/2, but not p38 or c-Jun NH2-terminal MAP kinases. Inhibition of ERK1/2 activation reduced the nicotine-induced OPN synthesis. Rats exposed to cigarette smoke showed a dose-dependent increase in pancreatic OPN that paralleled the rise of pancreatic and plasma nicotine levels. Analysis of cancer tissue from invasive PDA patients, the majority of whom were smokers, showed the presence of significant amounts of OPN in the malignant ducts and the surrounding pancreatic acini. Our data suggest that nicotine may contribute to PDA pathogenesis through upregulation of OPN. They provide the first insight into a nicotine-initiated signal transduction pathway that regulates OPN as a possible tumorigenic mechanism in PDA.